Remediation and Counter-Hegemony of Gender Dichotomy in Indonesian Family: Multimodal Discourse Analysis of Two Kecap Advertisements - Justito Adiprasetio; Annissa Winda Larasati (IKAT: The Indonesian Journal of Southeast Asian Studies, 2019)
Until now hegemonic gender dichotomyin Indonesia has worked in various spheres of human life, in various social roles, even in the smallest unitof social organizations: family. The dichotomy was caused by the ideology of "State Ibuism" which was disciplined during the New Order era between 1965 and 1998, where women would play the role of mothers as a subject of private work, serving various domestic needs of the family, while men play the right role conversely. Discipline works through various media formalized through the Marriage Act 1974, which explains the role of men and women in a married relationshipand Panca Dharma Wanita principles, which lays the foundation of theideal women. These ideals remained entrenched even after the New Order regime’s fall. Kecap ABC advertisements attempt to counter the hegemony over gender dichotomy and patriarchal division of work roles. This article uses Kress and Van Leeuwen’s multimodal discourse analysis to show how an attempt to counter ideologies wasmadeto be remediated through the modalities contained in these advertisements. This research elaborates on how these advertisements represent women as superior in terms of dealing with exploitation that occurs in a family, and shows how the renegotiation of domestic work is possible. This research also elaborates how the male body as a mediator of masculinity is actively mediated through modalities such as speech, gestures and moving images, by showing how men can also do domestic work.